Factors impacting the timing of reproductive development in female Antarctic krill at the northwestern Antarctic Peninsula - Steinke, Kirsten B.; Bernard, Kim S.; Reiss, Christian S.; Walsh, Jennifer; Correa, Giancarlo M.; Stammerjohn, Sharon E. (Frontiers in Marine Science, 2024)
The northwestern Antarctic Peninsula is an important spawning, recruitment, and overwintering ground for Antarctic krill. The region is warming rapidly, and the current impacts of climate and environmental variability on the reproductive cycle of krill remain unclear. Here, we examine the reproductive stage of female krill in the austral winter from 2012 to 2016 in relation to climate and environmental data to assess what factors influence the timing of reproductive development. We observed significant interannual variability in the degree of maturation in female krill, ranging from 48% of female krill measured at a station in 2016 to a maximum of 94% of female krill measured at a station in 2014. On average, across all five years, three-quarters of the female krill sampled were in the stage known as previtellogenesis, the point at which the onset of sexual maturity begins. The preceding spring, summer, and autumn Southern Annular Mode and the Multivariate El Niño Index explained most of the variance in the data and indicated a strong, preconditioning storm-related effect on environmental conditions leading up to winter, affecting krill maturation status at the end of the winter season. Results from our study can be used to improve krill population models that are necessary for the management of the krill fishery and for conservation at the northwestern Antarctic Peninsula.